Macromol. Rapid Commun. 18/2018. Issue 18 (19th September 2018) - Wang, Jiali; Rahman, Md. Mushfequr; Abetz, Clarissa; Rangou, Sofia; Zhang, Zhenzhen; Abetz, Volker
Abstract : Front Cover : In article number1800435 by Volker Abetz and co‐workers, polystyrene‐ block ‐poly(2‐hydroxyethyl methacrylate) (PS‐ b ‐PHEMA) membranes are fabricated by combining the self‐assembly of block copolymers with nonsolvent‐induced phase separation (SNIPS). For the first time, the pore size of the PS‐ b ‐PHEMA membranes is tailored between 10–20 nm without destroying the isoporous structure by two post‐treatment routes: thermal annealing and chemical modification.